ANALYSIS COMMON SIZE FOR ASSESSING FINANCES AT PT. AIR ASIA INDONESIA TBK - Merlita, Lala; Wooton, Ian; Nur Ilham, Rico; Sinta, Irada (PT. Radja Intercontinental Publishing, 2022)
This study aims to examine the assessing finances from 2019 to 2020, recording revenues fell and liabilities increased due to the implementation of PSAK 73 which requires every asset to be included in a liability account. The sample in this study is the aviation sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2020 period. Based on data from analysis of income statement financial statements using the common size method in 2019 and 2020, it can be concluded that the company's performance and finances were in a declining condition when the Covid-19 virus was increasing.In the disclosure of information, management stated that the contribution of income from operational activities that stopped or experienced restrictions to last year's total revenue was due to Business Profit (Loss) in which the efficiency program had been carried out by reducing operating expenses, but a significant decrease in operating income due to the impact of the Covid-19 pandemic causing the Company to record an operating loss of IDR 2.80 trillion in 2020 after the previous year it posted an operating profit of IDR 113.94 million.